Comparison of positron emission tomography diffusion‐weighted imaging (PET/DWI) registration quality in a PET/MR scanner: Zoomed DWI vs. Conventional DWI. Issue 4 (6th October 2015) - Sagiyama, Koji; Watanabe, Yuji; Kamei, Ryotaro; Baba, Shingo; Honda, Hiroshi
Abstract : Purpose: To compare zoomed diffusion‐weighted imaging (z‐DWI) with reduced field of view (FOV) by spatially selective radiofrequency pulses and conventional echo planar imaging (EPI) DWI (c‐DWI) with regard to registration quality using positron emission tomography / magnetic resonance (PET/MR) in patients with malignant tumors. Materials and Methods: Fludeoxyglucose (18 F ) PET imaging, c‐DWI, and z‐DWI were conducted simultaneously in 21 patients with known or suspected malignancy using a PET/MR system. A fusion image showing the largest tumor area was generated for analysis. Registration accuracy between PET and DWI was assessed based on the area of maximum overlap and central point displacement of the tumor. EPI factor, echo time (TE), matching area, and displacement were compared between c‐DWI and z‐DWI by paired t ‐test. Agreement of apparent diffusion coefficient (ADC) acquired by the two sequences were also assessed with linear regression s and Bland–Altman plot analysis. Results: Thirty‐two lesions were detected on both PET and DWI (mean size 536.3 ± 471.8 mm 2 ). At least one lesion was found in all subjects. In all cases, EPI factor was smaller with z‐DWI than c‐DWI (43.1 ± 15.6 vs. 62.0 ± 10.0, P < 0.0001), and TE was also shorter for z‐DWI (53.6 ± 3.6 msec vs. 65.2 ± 3.6 msec, P < 0.0001). Registration accuracy was better with z‐DWI in 30 of 32 lesions (93.8%), and both average matching area and central point displacement were significantly improved (79.8 ± 18.1% vs. 61.8 ± 22.9%, P < 0.0001 and 3.92 ± 2.69 mm vs. 7.51 ± 4.07 mm, P < 0.0001). ADC values calculated with c‐DWI and z‐DWI showed good agreement. Conclusion: Zoomed DWI reduces image distortion and provides better registration accuracy with PET images. J. Magn. Reson. Imaging 2016;43:853–858